Предмет: Алгебра,
автор: armanbeisembaev79
(5√5-√12)•(2-√5)+7√3=22√5-49+7√=
Ответы
Автор ответа:
1
Ответ:
(5×√(5−√(12)×(2−√(5)+7×√(3=225−49+7√))))
Автор ответа:
0
Ответ:
Объяснение:
(5√5 - √12) • (2 - √5) + 7√3 = 22√5 - 49 + 7
10√5 - 25 - 4√3 + 2√15 + 7√3 = 22√5 - 42
10√5 - 4√3 + 2√15 + 7√3 - 22√5 = -42 + 25
-12√5 + 3√3 + 2√15 = -17
Похожие вопросы
Предмет: Русский язык,
автор: nastya5286
Предмет: Русский язык,
автор: sab03rn2
Предмет: Русский язык,
автор: Princess1heroin
Предмет: Математика,
автор: frolovlexa
Предмет: ОБЖ,
автор: NumcevaKarina